Monoblastic Sarcoma- A Rare Case Report of Myeloid Sarcoma Variant - NUPUR KAUSHIK; LALIT KUMAR; POOJA AGARWAL; HARENDRA KUMAR; BRIJESH SHARMA (Journal of Clinical and Diagnostic Research, 2021)
Myeloid sarcoma, also known as chloroma, granulocytic sarcoma, extramedullary Acute Myeloid Leukaemia (AML), myeloblastoma or extramedullary myeloid tumour, is a rare manifestation, characterised by the proliferation of immature myeloid cells, myeloblasts or monoblasts occurring as one or more tumour at an extramedullary site. It is associated with disruption of normal architecture of tissue in which it is found. Monoblastic sarcoma is a rare variant of myeloid sarcoma. Hereby, the authors report a rare case of primary monoblastic sarcoma in a 64-year-old male patient presented with complaint of swelling over right side lower cervical region. He had no history of AML. On physical examination, the swelling was over medial one-third of right clavicle measuring 6×5.8×3 cm. The swelling was excised and sent for histopathological examination, which was diagnosed as monoblastic sarcoma, and confirmed on immunohistochemistry.